2022
DOI: 10.1007/s40122-022-00410-z
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of Add-on Mirogabalin to NSAIDs in Lumbar Spinal Stenosis with Peripheral Neuropathic Pain: A Randomized, Open-Label Study

Abstract: Introduction In Japan, conservative therapy for patients with lumbar spinal stenosis (LSS) includes non-steroidal anti-inflammatory drugs (NSAIDs), prostaglandin E1, tramadol, physical/exercise therapy, and nerve blocks. Mirogabalin, a selective oral α2δ ligand, is approved for treating peripheral neuropathic pain, though data regarding visual analog scores (VAS) for pain in patients with LSS are limited. We investigated the efficacy and safety of mirogabalin as an add-on treatment in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…NSAIDs are also considered one of the potentially inappropriate medications that can cause ADEs, especially for the elderly [ 19 , 20 , 21 ], so careful attention should be paid to the prescription of NSAIDs for LSCS patients, whether before or after lumbar surgery. Pregabalin/mirogabalin has been also reported to have a relatively high incidence of ADEs in patients with LSCS [ 22 , 23 ]. Common ADEs associated with pregabalin and mirogabalin are somnolence, dizziness, peripheral edema, and weight gain [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSAIDs are also considered one of the potentially inappropriate medications that can cause ADEs, especially for the elderly [ 19 , 20 , 21 ], so careful attention should be paid to the prescription of NSAIDs for LSCS patients, whether before or after lumbar surgery. Pregabalin/mirogabalin has been also reported to have a relatively high incidence of ADEs in patients with LSCS [ 22 , 23 ]. Common ADEs associated with pregabalin and mirogabalin are somnolence, dizziness, peripheral edema, and weight gain [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin/mirogabalin has been also reported to have a relatively high incidence of ADEs in patients with LSCS [ 22 , 23 ]. Common ADEs associated with pregabalin and mirogabalin are somnolence, dizziness, peripheral edema, and weight gain [ 22 , 23 ]. Especially in elderly patients with LSCS, physicians need to be aware of somnolence and dizziness caused by pregabalin/mirogabalin in terms of increased risk of falls.…”
Section: Discussionmentioning
confidence: 99%
“…Although this pain is frequently treated with gabapentinoids, such as pregabalin and gabapentin [ 38 ], there is insufficient evidence regarding their efficacy and safety in relation to central nervous system inhibition [ 39 ]. The relationship between neuropathic pain and COX-2 has been evaluated in an LPS-induced neuropathic animal model [ 40 ], and a recent randomized controlled trial reported that NSAIDs can improve peripheral neuropathic pain in LSS patients [ 41 ]. Therefore, GEO may act as a long-term modulator of neuropathic pain in patients with LSS, offering potential advantages over NSAIDs, which are recommended only for short-term use.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that in this patient group, the combination with diclofenac sodium, which suppresses nociceptive pain, may have resulted in additional pain improvement compared with the non-combination group (placebo group), resulting in a greater change in pain VAS scores. Furthermore, one study reported that the addition of the α2δ Ca 2+ channel ligand mirogabalin in patients treated with NSAIDs for lumbar spinal canal stenosis with peripheral neuropathic pain significantly improved the change in pain VAS scores compared with patients treated with NSAIDs alone [ 14 ], and another found that the combination of celecoxib and pregabalin was more effective than monotherapy [ 10 ]. Although these reports do not directly support an additive effect of the DF systemic patch itself with α2δ Ca 2+ channel ligands, the positive effects of the concomitant use of NSAIDs and α2δ Ca 2+ channel ligands indicate that the DF systemic patch may also be highly likely to have an additive effect in controlling chronic pain, such as that associated with the mixed pain of chronic low back pain.…”
Section: Discussionmentioning
confidence: 99%